If you take the logarithm of a negative number, you will get a complex number (I will not give you the proof - that is for you to figure out). But what is even more mind-boggling is that you will get an infinite number of complex numbers.
For example, if we were to evaluate lo g 2 ( − 8 ) we could get the following numbers: 3 + 4 . 5 3 2 3 6 i , 3 + 4 0 . 7 9 1 2 4 i , 3 − 6 7 . 9 8 5 4 0 i , . . .
Let lo g 2 ( − 1 0 2 4 ) = a + b i where a and b are real numbers and ∣ b ∣ is minimized. There are two solutions a + b i that satisfy these requirements. What is the product of these two solutions, rounded to three decimal places?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Euler's formula tells us that e ( 2 k − 1 ) π i = − 1 for any integer k . From this, if we take the natural logarithm of both sides, we get ln ( − 1 ) = ( 2 k − 1 ) π i . We can get the general form ln ( − n ) using the property ln ( a b ) = ln ( a ) + ln ( b ) . Since ln ( − n ) = ln ( n ∗ − 1 ) = ln ( n ) + ln ( − 1 ) , we conclude that ln ( − n ) = ln ( n ) + ( 2 k − 1 ) π i . Dividing all sides by ln ( 2 ) gives us the formula lo g 2 ( − n ) = lo g 2 ( n ) + ln ( 2 ) ( 2 k − 1 ) π i .
Thus, the two solutions are 1 0 + ln ( 2 ) π i and 1 0 − ln ( 2 ) π i and their product is ( 1 0 + ln ( 2 ) π i ) ( 1 0 − ln ( 2 ) π i ) = 1 0 0 + ln 2 ( 2 ) π 2 = 1 2 0 . 5 4 2
@Alexander McDowell , the first statement "If you take the logarithm of a negative number, you will get an i m a g i n a r y number" is incorrect. It should be " c o m p l e x number". Imaginary numbers don't have the real part.
It has been fixed
lo g 2 ( − 1 0 2 4 ) = lo g 2 ( 1 0 2 4 ) + lo g 2 ( − 1 ) = 1 0 + lo g ( 2 ) lo g ( − 1 ) = 1 0 + lo g ( 2 ) lo g ( e ± π i ) Two solutions are y 1 = 1 0 + lo g ( 2 ) π i , y 2 = 1 0 − lo g ( 2 ) π i y 1 . y 2 = 1 0 2 + lo g 2 ( 2 ) π 2 = 1 2 0 . 5 4 2 2
Problem Loading...
Note Loading...
Set Loading...
lo g 2 ( − 1 0 2 4 ) = ln 2 ln ( − 2 1 0 ) = ln 2 ln ( 2 1 0 ( − 1 ) ) = ln 2 ln ( 2 1 0 e ± i π ) = ln 2 1 0 ln 2 + ln e ± i π = 1 0 ± ln 2 π i Convert base 2 to base e By Euler’s formula: e i θ = cos θ + i sin θ Note that lo g ( a b ) = lo g a + lo g b
Then ( 1 0 + ln 2 π i ) ( 1 0 − ln 2 π i ) = 1 0 2 + ( ln 2 π ) 2 ≈ 1 2 0 . 5 4 2 .
Reference: Euler's formula